Isolation and Identification of Vancomycin-resistant Staphylococcus aureus - A. Mahmood, Hawraa; T. Flayyih, May (Iraqi Journal of Science, 2023)
Susceptibility of thirty seven clinical isolates of Staphylococcus aureus to various antibiotics was tested. 100 % of tested isolates were resistant to ampicillin, while the lowest resistance recorded to amikacin 8.10 %. Four of S. aureus isolates showed resistant to vancomycin. Minimum inhibitory concentration (MIC) of isolates 33 and 56 for vancomycin was ≥ 32 μg/ml.